Analysis And Evaluation of Momentary Forces and Reaction Time on The Starting Cushions with Sensors - Dynamic for Runners - Maher Shlash; Sareeh Alfadly (College of Physical Education and Sport Sciences, 2023)
Starting cubes are a device used in the sport of arena and field races by speed-racing athletes to strengthen and stabilize their feet at the beginning of the race so as not to slip forward when hearing the starting gun. How can they improve the payment on these cubes? Why is starting important in fast running? When it comes to starting the race, athletes with the best reaction time, greatest strength, and the ability to accelerate as fast as possible can outperform their peers. It is important to remember one essential thing: when cubes are used, they should be intended to be able to help and allow the runner to accelerate, not to get him to full speed in the first few steps. Young athletes, therefore, tend to try to reach as quickly as possible once they start from the starting blocks. So, the starting cubes are designed to give runners great horizontal momentary strength, the most important indicator in the starting cubes is to get the right body angles. This research provides further developments and takes advantage of the start of the run to evaluate and analyze the forces and reaction time obtained by the movements of the two men on the cubes of starting the various fast running races (100m, 100m women's barriers), Men's 110mHurdles, 200m, 400m,400m Hurdles, 4×100m Relay, 4×400m Relay, 4x100m Mixed) For different categories. The idea of designing sensors -  dynamic on the starting cubes came to the necessary need for such sensors that measure the amounts of power propulsion and reaction time of runners in these events taking advantage of the technology and scientific development in this field, if the start-up cushions are designed with sensors  - dynamic and calibrated mechanically standard to provide the required measurement accuracy  It was used to measure and analyze the strength and reaction time of the enemies of these elite Iraqi competitions by basing lab view workers, and the measured results obtained showed reasonable sensitivity and accuracy with a slight variation in their values, as well as measuring the change in strength over time for Runners perform this launch and acceleration based on the computer's vision tracking system. The proposed start-up cushions are promising to be used in a wide range of applications, including in-house and field laboratories for teaching, training, and monitoring the progress of runners during training and scientific research.